2013
DOI: 10.3184/175815513x13802978348434
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cd with or without se Supplementation on Spermatogenesis and Semen Quality in the Rooster (Gallus gallus)

Abstract: In human and animals, it has been reported that Cd was linked with a number of health problems including marked damage of testes and fertility reduction. As for the sensitivity of fowl testes to Cd the results published so far differ from those reported in mammalian species. In this experiment, the effect of Cd with and without Se on spermatogenesis and semen quality in the rooster was studied after dietary Cd uptake. Cadmium (Cd) as Cd chloride (CdCl 2 ) and Se (Se) as sodium selenite (Na 2 SeO 3 ) were added… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…In first experiments with Japanese quail vascular damage was not evident, though the spermatogenic cells did fail to mature (Richardson et al, 1974). In later studies the testicular changes observed in cocks, in many aspects, were similar to those in mammals (Li et al, 2010;Marettová et al, 2013).…”
Section: Toxicity Of CD On Blood Vesselsmentioning
confidence: 63%
See 3 more Smart Citations
“…In first experiments with Japanese quail vascular damage was not evident, though the spermatogenic cells did fail to mature (Richardson et al, 1974). In later studies the testicular changes observed in cocks, in many aspects, were similar to those in mammals (Li et al, 2010;Marettová et al, 2013).…”
Section: Toxicity Of CD On Blood Vesselsmentioning
confidence: 63%
“…Edema, necrosis and degeneration of seminiferous tubules were frequently reported in fowl (Bokori et al, 1996;Marettová et al, 2013). Spermatogenic cells underwent irreversible degeneration or atrophy in the absence of significant vascular lesions.…”
Section: Vascu Lar Smooth Muscle Cell Smentioning
confidence: 95%
See 2 more Smart Citations
“…The reproduction system of cocks was also affected by Cd toxicity in the study of Li et al (2010), who observed that a high dose of Cd (150 mg of Cd/kg of feed) affected the interstitial oedema and partial loss of spermatogenic cells and the number of apoptotic cells in the testes significantly increased. A more recent study by Marettova et al (2013) indicated that a lower dose of Cd (20 mg of Cd/kg of feed) caused structural changes in the testis and in the qualitative properties of the semen.…”
Section: Adverse Effects Of CD On Poultry Performancementioning
confidence: 99%